Set Design Module Development Based on Guided Discovery Learning Model - Nuraini, Rohma; Suparman, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
Understanding basic concepts in problem solving is very important for students. This will affect the student learning experience. This study aims to design modules to improve students’ ability to find basic concepts that will be used in problem solving. The method used is the ADDIE model which consists of analyze, design, development, implementation. This research is only limited to two stages, namely the Analyze and Design stages. Data collection instruments in the form of questionnaires, observation guidelines, and interviews. The subjects of this study were teachers and junior high school students. This study resulted in the design of learning modules in accordance with student characteristics, curriculum analysis, and concept / material analysis. This design has the advantage of improving the understanding of students’ basic concepts in problem solving which refers to learning based on Guided Discovery.